Magnetic resonance monitoring of focused ultrasound/magnetic nanoparticle targeting delivery of therapeutic agents to the brain - Liu, Hao-Li; Hua, Mu-Yi; Yang, Hung-Wei; Huang, Chiung-Yin; Chu, Po-Chun; Wu, Jia-Shin; Tseng, I-Chou; Wang, Jiun-Jie; Yen, Tzu-Chen; Chen, Pin-Yuan; Wei, Kuo-Chen; Weissleider, Ralph (Proceedings of the National Academy of Sciences - PNAS, 2010)
The superparamagnetic properties of magnetic nanoparticles (MNPs) allow them to be guided by an externally positioned magnet and also provide contrast for MRI. However, their therapeutic use in treating CNS pathologies in vivo is limited by insufficient local accumulation and retention resulting from their inability to traverse biological barriers. The combined use of focused ultrasound and magnetic targeting synergistically delivers therapeutic MNPs across the blood–brain barrier to enter the brain both passively and actively. Therapeutic MNPs were characterized and evaluated both in vitro and in vivo, and MRI was used to monitor and quantify their distribution in vivo. The technique could be used in normal brains or in those with tumors, and significantly increased the deposition of therapeutic MNPs in brains with intact or compromised blood–brain barriers. Synergistic targeting and image monitoring are powerful techniques for the delivery of macromolecular chemotherapeutic agents into the CNS under the guidance of MRI.